2006
DOI: 10.1007/s10697-006-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Vortex structure generation on the frontal surface of a cylinder set transversely in a hypersonic flow

Abstract: The problem of formation of spatially periodic structures on the frontal surface of a cylindrically blunted body set transversely in a hypersonic flow is studied. Within the framework of the model adopted, a possible mechanism of vortex structure generation on the frontal surface of the blunt body is proposed and confirmed by calculations; in this mechanism, the curved bow shock produces a vortex flow, while in its turn the vortex, which persists under weak dissipation, acts on the shock thus maintaining its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In particular, along with the plane flow mode (Fig.1a), three-dimensional steady-state vortex structures (Fig.1b) were revealed in some calculations and experiments related to transverse hypersonic flows past bodies with a cylindric frontal bluntness. [1][2][3][4][5] One can distinguish three basic mechanisms representing physical reasons for the development of such structures: I) external excitation of vortices induced by spatial inhomogeneity of the free stream or boundary conditions on the body; II) internal excitation caused by the development of transverse flow instability in the neighborhood of the leading stagnation line (Taylor-Görtler instability, for example) 2 ; III) self-generation of spanperiodic structures under homogeneous external conditions supported by a strong interaction between the bow shock and the vortex flow in the compressed layer. [3][4][5] The fact that vortex structures can appear as a result of external impact is theoretically understood and in the present study the first mechanism is considered only as one way of initial perturbation of the primary (plane) flow mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, along with the plane flow mode (Fig.1a), three-dimensional steady-state vortex structures (Fig.1b) were revealed in some calculations and experiments related to transverse hypersonic flows past bodies with a cylindric frontal bluntness. [1][2][3][4][5] One can distinguish three basic mechanisms representing physical reasons for the development of such structures: I) external excitation of vortices induced by spatial inhomogeneity of the free stream or boundary conditions on the body; II) internal excitation caused by the development of transverse flow instability in the neighborhood of the leading stagnation line (Taylor-Görtler instability, for example) 2 ; III) self-generation of spanperiodic structures under homogeneous external conditions supported by a strong interaction between the bow shock and the vortex flow in the compressed layer. [3][4][5] The fact that vortex structures can appear as a result of external impact is theoretically understood and in the present study the first mechanism is considered only as one way of initial perturbation of the primary (plane) flow mode.…”
Section: Introductionmentioning
confidence: 99%
“…The third mechanism was proposed in works 3,4 where it was shown that in case of transverse hypersonic (M ∞ ≥ 5) flow past bodies with cylindrical bluntness of the frontal surface, a steady-state 3D flow mode consisting of paired vortices that are periodic along Z axis of the cylinder can exist simultaneously with a plane (two-dimensional) mode. Physical essence of the third mechanism is the following.…”
Section: Introductionmentioning
confidence: 99%